2005
DOI: 10.1086/426734
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a Major Locus that Determines Telomere Length in Humans

Abstract: Telomere length is a crucial factor for both normal chromosomal function and senescence. Mean telomere length in humans shows considerable interindividual variation and strong genetic determination. To see if a locus (or loci) affecting telomere length in humans could be mapped, we performed a quantitative-trait linkage analysis of mean leukocyte telomere-restriction-fragment (TRF) lengths, measured by Southern blotting, in 383 adult subjects comprising 258 sib pairs. Heritability of mean (+/-SE) TRF was 81.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
211
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(228 citation statements)
references
References 22 publications
11
211
2
4
Order By: Relevance
“…Several studies have investigated the heritability of LTL in twin and family studies. As in our study, the majority of these studies have indicated that LTL has a strong genetic component in (11,28,29). A recent meta-analysis reported a heritability estimate of 70% for LTL (11).…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have investigated the heritability of LTL in twin and family studies. As in our study, the majority of these studies have indicated that LTL has a strong genetic component in (11,28,29). A recent meta-analysis reported a heritability estimate of 70% for LTL (11).…”
Section: Discussionsupporting
confidence: 79%
“…Another study comprising 258 sib-pairs returned a heritability estimate of 82%. 21 There is a need to reconcile these divergent estimates, which might in part be caused by differences in sample composition or TL assessments. 22 A remaining question that also needs to be addressed is the extent to which estimates of heritability based on twin data are comparable to those based on other relatives such as parents and offspring from multigenerational studies or non-twin sibling pairs.…”
Section: Introductionmentioning
confidence: 99%
“…3 Telomere length varies between individuals of the same age, and is found to be inheritable in quantitative-trait linkage analyses of sib pairs. 4,5 Quantitative trait locus studies have mapped putative loci for telomere length to human chromosomes 3p26.1, 10q26.13, 12q12.22 and 14q23.2. [5][6][7] Telomerase is a large, mainly uncharacterized, RNA-protein complex that is responsible for the de novo synthesis and maintenance of telomere ends.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Quantitative trait locus studies have mapped putative loci for telomere length to human chromosomes 3p26.1, 10q26.13, 12q12.22 and 14q23.2. [5][6][7] Telomerase is a large, mainly uncharacterized, RNA-protein complex that is responsible for the de novo synthesis and maintenance of telomere ends. TERC is a main component of telomerase, which serves as a template for addition of multiple 6 bp (TTAGGG) telomere repeats.…”
mentioning
confidence: 99%